Duality, urbanization, and modernization of agrifood systems in Latin America and the Caribbean - Díaz-Bonilla, Eugenio; Echeverria, Ruben G. (International Food Policy Research Institute, 2021)
The agriculture sector in Latin America and the Caribbean (LAC) is certainly not homogeneous, covering a variety of very different agroecological and climate zones, along a south-north axis.1 There are three large agricultural producers: Brazil (close to 48 percent of total agricultural production in the region on average during the 2010s), Argentina (almost 14 percent), and Mexico (about 12 percent), along with several intermediate and small producers, which, added together, have as much agricultural production as Argentina and Mexico combined. Within that diversity, it is possible to identify three broad agricultural situations, a product of geography and climate, the historical occupation of space during the period of discovery and settlement of the Americas, and the different cycles of integration in global markets.